Analisis Nilai Wajar Tarif Masuk Kebun Raya ITERA Menggunakan Contingent Valuation Method: Willingness To Pay - Pamelih Wongsoatmojo; Martha Indra Kusuma; Paulus Agung Cahya Wahyudi; Kiki Nurman Setiawan; Murtaji Murtaji (JURNAL AKUNTANSI DAN MANAJEMEN MUTIARA MADANI, 2023)
ITERA Botanical Garden have been operating and it requires funding support for maintenance in order to maintain its service optimally. Therefore, we conduct an analysis of visitors Willingness to Pay (WTP) for the entrance fee to the ITERA Botanical Gardens and later on it can be used as a reference in determining the Entrance Ticket Price as the basic service fee. Previous studies shown that the Contingent Valuation Method (CVM) can be used to determine the value of tariffs/contributions for such given good and services. In this study, a survey was conducted among visitors to the ITERA Botanical Gardens. Our research shows that 57% of respondents were willing to pay, while the remaining 43% were not willing to pay because it was too expensive, they could not afford it, or they were not sure that the tariff of the retribution would be used properly to manage the garden. Based on analysis, the WTP obtained through the Turnbull Method is greater, resulting IDR 11,875.00 per person per visit, while the WTP value obtained through the logit model is IDR 10,438.00 per person per visit. Keywords: fair value, contingent valuation method, willingness to pay, Kebun Raya ITERA Botanical Garden have been operating and it requires funding support for maintenance in order to maintain its service optimally. Therefore, we conduct an analysis of visitors Willingness to Pay (WTP) for the entrance fee to the ITERA Botanical Gardens and later on it can be used as a reference in determining the Entrance Ticket Price as the basic service fee. Previous studies shown that the Contingent Valuation Method (CVM) can be used to determine the value of tariffs/contributions for such given good and services. In this study, a survey was conducted among visitors to the ITERA Botanical Gardens. Our research shows that 57% of respondents were willing to pay, while the remaining 43% were not willing to pay because it was too expensive, they could not afford it, or they were not sure that the tariff of the retribution would be used properly to manage the garden. Based on analysis, the WTP obtained through the Turnbull Method is greater, resulting IDR 11,875.00 per person per visit, while the WTP value obtained through the logit model is IDR 10,438.00 per person per visit.